EVALUASI PENEMPATAN TRANSFORMATOR-DISTRIBUSI BERDASARKAN KESEIMBANGAN BEBAN - Winardi, Bambang (Transmisi, 2008)
Therea re two main distributions ystemsth e primary and secondaryd istribution netwo*s. The primaryo r midle volage nenvorks2 0 kV compriseth e networks& om main stationso f transformatortso distributions tationss ides, the secondaryo r lower voltage networks2 2013 80 V containsth e power line networksf rom distibution stationsu ntil the customerosr loadsi nstalation.Thdei stributionn etworksis the closeset lectricapl owers ystem to thec ustomerosr loadss ided iferenwt ith thet ransmissionne tworks. ln Indonesiath e electricanl etworksc onditionh ave5 o/od ropv oltage( VD) influenceb y many facton one of them is unoptimizedtr ansformatopr lacementto the load side. The far the distanceth e more voltaged rop will be and the maximumo f l0o/oo f drop voltages hould anticipateth e 22,7o/of electricall oad increasingA. ccordingt o that condition,t he needo f evaluationa ndr eplanningd ependo n somea llowedc riteriasis imporantf or thec ontinuitya nd efficienot f thee lectricaplu blics ervice. Â  Keywords:d istributions ysteml,o adb alancinglo, ssesf,iz nsformatoprl acement.